Penerapan Kebijakan Artificial Intelligence, Digitalisasi dan Rasionalisasi Industri Asuransi oleh Otoritas Jasa Keuangan RI - Karso, A. Junaedi (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
To support the digitization  of Artificial Intelligence in the life insurance industry, OJK Regulation Number 13/POJK.02/2018 was issued concerning Digital Financial Innovation in the Financial Services Sector. This regulation contains provisions that oversee the supervision and regulation of the digital financial industry that transforms in business processes and the provision of services to consumers by optimizing the use of digital tools," he said. Government support is a breath of fresh air for the insurance industry to develop its business towards digital or insurance technology (insurtech). Rationality in Investing As previously reported, the relaxation of the easing of the premium payment deadline is regulated in OJK Letter Number S-11/D.05/2020 dated March 30, 2020. In this regulation, the OJK provides relaxation for all insurance, reinsurance, sharia insurance, and sharia reinsurance companies to extend the deadline to policyholders for 4 months from the original 2 months from maturity. There are three important things to consider before choosing an insurance product. First, prospective policyholders need to map out what needs they want to cover by having an insurance product. The right insurance product is one that suits the needs of its policyholders. For this reason, prospective policyholders also need to understand what a product offers, namely: 1). Adjust needs; 2). Second, what needs to be considered is, the availability of additional services provided by the insurance company; 3) The reputation of the insurance company. The things that need to be considered if a health insurance claim is rejected by an insurance company, including: 1). Claims that do not meet the policy provisions; 2). Claims filed outside the provisions of the policy; 3). The policy is in a lapse condition; 4). Completeness of documents that are not fulfilled; (5). Claims are included in the exclusion; 6). The claim has not passed the waiting period.